(untitled) (Medico Legal Update, 2020)
Introduction: In era of National Health Insurance, the number of insurance participants was in increase and recorded approximately about 203,28 million (77%) from the total population of Indonesia, this condition affected to the invoice amount which must be paid by Social Insurance Administration Organization (BPJS) to the related hospital which partnered with this organization. The implementation of this deal delivered to good effects from either the hospital or related organization(11). In Jember, it was indicated retardation or delay of service payment in certain hospitals. The retardation of service payment was very influential to the work motivation of employee which affected to the quality of service, the employee motivation was very significant to build quality performance for the employee. The accurate illustration which depicted this relation was that the motivation could raise high work satisfaction on employee, this condition was realized if the employee’s expectation and need could be realized in both material and non-material, if those were fulfilled, then their work motivation would be built. The objective of this research was to analyze the effects of service payment retardation from National Health Insurance claim to the motivation of employee based on Frederick Hezberg’s theory in RSD Balung. Method: This research was included into quantitative research which exerted cross sectional research method. The total population of this research were all employees in RSD Balung Jember District, specifically in about 157 respondents. The method of data sampling was stratified random sampling according to the level within this research population. The total sample of this research was 60 respondents(15). Further, the data collection was employed through questionnaire and was then analyzed through ordinal regression. Based on the research finding, it showed effects between service payment retardation from National Health Insurance claim to the employee’s motivation accordingly to theory of Frederic Hezberg.